Exploring the Fusion of Specialty Coffee for Tourism Growth in Makkah and Madinah - Maspul, Kurniawan Arif (Advances in Tourism Studies, 2024)
The integration of specialty coffee in the holy cities of Makkah and Madinah offers a unique opportunity to enhance the visitor experience, drive economic growth, foster cross-cultural exchange, and promote sustainability. This qualitative study explores the multifaceted aspects of specialty coffee in these revered cities through interviews, site visits, and thematic analysis. Specialty coffee shops provide a delightful addition to pilgrims' spiritual journeys, offering a balance of calm, enjoyment, and indulgence. The economic potential of the specialty coffee sector can lead to diversification, job creation, and entrepreneurial opportunities. By promoting indigenous coffee types and preserving cultural practices, Makkah and Madinah can become cultural hotspots globally. Understanding consumer preferences can guide effective marketing strategies, positioning Saudi specialty coffee in the global market and attracting coffee enthusiasts worldwide. The growth of the specialty coffee market also promotes sustainability through fair trade and responsible practices, benefiting local coffee growers and contributing to an environmentally responsible industry. This study emphasizes the importance of expanding the specialty coffee market in Makkah and Madinah, providing valuable insights and recommendations for cultural and economic enrichment in these sacred cities.